ASIAN MONEY: A NEW QUALITY - SALITSKIY, Alexander (CENTRAL ASIA AND THE CAUCASUS, 2004)
Rephrasing Mao Zedong, we could say that Eastern money is getting the better of Western money. This refers to a rather unusual situation that has evolved in the world economic and financial system in the new millennium. To evaluate the lineup of forces in the global economy as well as the role that the Central Asian republics and Russia could play in this economy, we need to make a brief digression into the economic development period that began after World War II. In the 1950s, world GDP growth rates sharp-ly increased, to 5.0 percent, including to 4.1 percent in developed states and 5.2 percent in developing countries.1 In the West, the main factors in this process were the reconstruction of national economies and the introduction of essential innovative technology (nuclear energy, petrochemistry, jet aviation, television, etc.). In addition, the normalization of international trade and the evolution of capitalism itself, whose contradictions were losing their antagonistic character, also played a role here. Formation of the welfare state reduced inequality in income distribution, which for its part expanded the domestic market, facilitating mass consumption. the same time, Western ruling circles reviewed their approaches toward the periphery. The relative depreciation of fixed capital in developed states and the anticipated expansion of the foreign market 2 had, by the early 1960s (as industrialization gained ground), created an economic base for the provision of development aid to peripheral (economically speaking) countries, including state credits, personnel training programs, etc. In the 1950s-1960s, however, economic growth rates in developing countries were mainly based on internal factors. Achievement of political independence, elimination of discrimination, liquidation of extra-economic coercion, reduction in the claw-back of the net product, the lifting of restrictions on external competition, and other measures implemented at the time created favorable conditions for economic revival in these countries. The role of the nation-state modified. It eliminated the most archaic relations, put in place the essential elements of infrastructure and industry, and pro-moted domestic enterprise. In a number of small countries and territories, the state was highly instrumental in launching export orientation mechanisms.